(untitled) (Revista LIDER, 2020)
The research studies the possibility of promoting the economic development in Apia (Risaralda) through the boost of intangible capitals, at the same time that studies some characteristics of the “Association of Producers from Apia” (ASOAPIA), organization that would search to present a proposal to incorporate it into the municipality’s development plan. The constitutes the theoretical base of the investigation in its first part; the study of some characteristics of ASOAPIA’s associatesmolds its second part. Finally, a group of four experts linked to the academic, political and economic sector were interviewed who recommended that the local development plan of Apia, based in associativity, was to be boosted through educational processes and these developments incorporated, to the new outline of the territorial order and to the future plans of municipal development.